2011
DOI: 10.1002/adsc.201100530
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative to Nitromethane as Solvent: The Promoting Influence of Nitro‐Functionalized Imidazolium Salts for Synthesis and Catalysis

Abstract: Nitromethane, a volatile and toxic organic compound, is commonly used as solvent for organic and catalytic reactions. In order to find an alternative for this specific nitro-containing organic solvent, the performance of some nitro-functionalized imidazolium salts such as 1-methyl-3-(4-nitrobenzyl)imidazolium hexafluorophosphate, 1-methyl-3-(4-nitrobenz-A C H T U N G T R E N N U N G yl)imidazolium tetrafluoroborate, 1-methyl-3-(4-nitrobenzyl)imidazolium bis(trifluoromethanesulfonyl)-A C H T U N G T R E N N U N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…When (S)-5 a was treated with an excess amount of boron trifluoride etherate in the presence of pbromobenzenethiol in CH 2 Cl 2 , the chiral sulfide 7 was obtained in 77 % yield with 91 % chirality transfer. [16] The absolute configuration of the major enantiomer of 7 was determined to be R. [17] It was confirmed that the present reaction proceeded with inversion of the configuration at the benzylic carbon.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…When (S)-5 a was treated with an excess amount of boron trifluoride etherate in the presence of pbromobenzenethiol in CH 2 Cl 2 , the chiral sulfide 7 was obtained in 77 % yield with 91 % chirality transfer. [16] The absolute configuration of the major enantiomer of 7 was determined to be R. [17] It was confirmed that the present reaction proceeded with inversion of the configuration at the benzylic carbon.…”
mentioning
confidence: 65%
“…Subsequent transfer hydrogenation of the ion-pair intermediate 6 afforded the chiral isochromene 5. [16] The absolute configuration of the major enantiomer of 7 was determined to be R. [17] It was confirmed that the present reaction proceeded with inversion of the configuration at the benzylic carbon. [14,15] Further transformation of the chiral isochromenes was explored (Scheme 3).…”
mentioning
confidence: 70%
“…For safety and environmental reasons, we continued the reactions with ethanol. Further investigation revealed that the reaction was also affected by the other parameters including catalyst amount, temperature, and reaction time, and the optimal conditions should be 1.2 mol % of LS-Sc I, 808C, and 8 h (entries [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, several safer alternatives to classic dipolar aprotic solvents have been reported recently. We proposed the use of a NO 2 ‐functionalized imidazolium‐based ionic liquid as a solvent (or a solvent system component) to replace nitromethane, which is an explosive dipolar and aprotic solvent . Some interesting options have also been found in the field of bio‐based chemicals, such as cyrene ((−)‐dihydrolevoglucosenone), N ‐butylpyrrolidinone, γ‐valerolactone or 2‐methyltetrahydrofuran (2‐MeTHF) .…”
Section: Introductionmentioning
confidence: 99%